1998
DOI: 10.1172/jci1617
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of mice deficient in hepsin, a hepatic transmembrane serine protease.

Abstract: Hepsin is a type II transmembrane serine protease highly expressed on the surface of hepatocytes. The physiological function of hepsin is not known, although in vitro studies indicate that hepsin plays a role in the initiation of blood coagulation and in hepatocyte growth. To determine the functional importance of hepsin, we generated hepsin-deficient mice by homologous recombination. Homozygous hepsin-/- mice were viable and fertile, and grew normally. In functional assays including tail bleeding time, plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 39 publications
5
79
1
Order By: Relevance
“…A proteolysis-independent role of HAI-1 in embryonic development has also been proposed (Tanaka et al, 2005), because HAI-1 is an integral transmembrane protein with a cytoplasmic tail domain that is potentially capable of transducing extracellular signals, and because hepatocyte growth factor activator, hepsin, and matriptase are all dispensable for mouse embryonic development (Wu et al, 1998;List et al, 2002;Itoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A proteolysis-independent role of HAI-1 in embryonic development has also been proposed (Tanaka et al, 2005), because HAI-1 is an integral transmembrane protein with a cytoplasmic tail domain that is potentially capable of transducing extracellular signals, and because hepatocyte growth factor activator, hepsin, and matriptase are all dispensable for mouse embryonic development (Wu et al, 1998;List et al, 2002;Itoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, hepsin colocalizes with desmoplakin at the sites of desmosomal junctions. 9 Previously, Wu et al 10 and our group 11 successfully deleted the hepsin gene (hepsin À/À ) in mice and generated hepsin À/À mice that are viable, fertile, and grow normally, suggesting that hepsin is not essential for normal development. No significant differences in coagulation function or liver regeneration ability were found in hepsin À/À and wild-type (WT) littermates.…”
mentioning
confidence: 99%
“…Despite its expression in the very early stages of embryogenesis (2), hepsin-deficient mice were viable and developed normally (3,4). The studies further showed that hepsin was not essential for liver regeneration and for coagulationrelated physiological functions (3,4). However, hepsin has been implicated in ovarian cancer (5) and prostate cancer (6 -11), where several gene expression studies have identified it as one of the most highly induced genes.…”
mentioning
confidence: 99%